Floristic and Structural Study of the Dahliafleur Partial Nature Reserve Located in Bingerville (Côte d’Ivoire) - Koffi, Missa; Kafana, Soro; Leonie, Kanga Ami; Jean, Koffi Kouao (European Scientific Journal, ESJ, 2022)
The Dahliafleur Partial Nature Reserve, located in the town of Bingerville, is part of the great Ivorian protected area network. Unfortunately, very little is known about its floristic diversity, and even less about the structure of its vegetation. This work intends to characterize its floristic and structural aspects, through 13 surface surveys and an itinerant survey carried out in the northern, central and southern zones of this area. The data analysis revealed that the Dahliafleur Partial Nature Reserve includes 135 species. These species are divided into 110 genera and 53 families. It has 26 special-status species and the highest diversity index of any urban forest. The diametric structure shows histograms in the shape of an "inverted J" for each of the areas. This pattern is typical of a forest in a good state of conservation and with good regeneration capacity.